Improvement of early detection of breast cancer through collaborative multi-country efforts: Medical physics component - Mora Rodríguez, Patricia (2018)
Purpose: The International Atomic Energy Agency (IAEA) through a Coordinated Research Project on “Enhancing Capacity for Early Detection and Diagnosis of Breast Cancer through Imaging”, brought together a group of mammography radiologists, medical physicists and radiographers; to investigate current practices and improve procedures for the early detection of breast cancer by strengthening both the clinical and medical physics components. This paper addresses the medical physics component. Methods: The countries that participated in the CRP were Bosnia and Herzegovina, Costa Rica, Egypt, India, Kenya, the Frmr. Yug. Rep. of Macedonia, Mexico, Nigeria, Pakistan, Philippines, Slovenia, Turkey, Uganda, United Kingdom and Zambia. Ten institutions participated using IAEA quality control protocols in 9 digital and 3 analogue mammography equipment. A spreadsheet for data collection was generated and distributed. Evaluation of image quality was done using TOR MAX and DMAM2 Gold phantoms. Results: QC results for analogue equipment showed satisfactory results. QC tests performed on digital systems showed that improvements needed to be implemented, especially in thickness accuracy, signal difference to noise ratio (SDNR) values for achievable levels, uniformity and modulation transfer function (MTF). Mean glandular dose (MGD) was below international recommended levels for patient radiation protection. Evaluation of image quality by phantoms also indicated the need for improvement. Conclusions: Common activities facilitated improvement in mammography practice, including training of medical physicists in QC programs and infrastructure was improved and strengthened; networking among medical physicists and radiologists took place and was maintained over time. IAEA QC protocols provided a uniformed approach to QC measurements.